Goodbye to the dead - Freeman, Brian, 1963- (Freeman, Brian, 1963- Jonathan Stride novel., 2016)
Detective Jonathan Stride's first wife, Cindy, died of cancer eight years ago, but her ghost hangs over Stride's relationship with current lover, and fellow detective, Serena Dial.